Do VTOL Aircraft create an inherently more Problematic Downwash than Conventional Helicopters? - Brown, R.E. (My University, 2023)
Extensive worldwide interest in the rotorcraft industry currently exists in developing small, lightweight, electrically-propelled multi-rotor craft, typically capable of carrying four to six passengers on short-range intra-urban missions, for instance as part of a passenger ferry service between an airport and a downtown commuter hub. The potential for the flows generated by helicopter rotors to create significant upset in the vehicle’s surroundings has long been appreciated by the rotorcraft community, yet very little has been written, until recently, about the structure of the downwash field that these new eVTOL aircraft will create, and how this field might interact with the ground during landing and take-off. A new numerical study suggests that the interactions between the multiple wakes of the rotors of some of these vehicles could amplify and modify key features of the field, especially when it interacts with the ground and turns to outwash. Indeed, the study suggests that the flow out across the ground that is generated by these vehicles could potentially be very different in character and strength to that which is produced by conventional helicopters. We discuss some of the potential implications of these findings for the developers and operators of these new aircraft, as well as for the designers of the vertiports at which they will begin and end their journeys.
Keywords: Urban Air Mobility